Ernährung und Sport - Kratzenstein S; Carlsohn A; Heydenreich J; 4; Mayer F (Deutsche Zeitschrift für Sportmedizin, 2016)
Objective: Information about dietary supplement (DS) use in young German athletes beginning their sporting career is scarce and possible differences to their non-athlete counterparts are unknown. Therefore, the purpose of this study was to analyze DS use in young elite German athletes (A) and non-athlete (NA) controls.Method: During pre-participation examinations, 562 athletes (323m/239f, 11.70.6 years) and 69 non-athletes (12m/57f; 12.50.5 years) answered a standardized questionnaire analyzing the prevalence of DS use, reasons for intake, and sources of information. Group differences were analyzed with Chi test (=0.05).Results: 14% of A and 20% of NA used DS, with no statistically significant differences between groups (p=0.231). Magnesium (A: 35%; NA: 36%) and calcium (A: 28%; NA: 7%) were the most frequently used minerals. Vitamin C (A: 37%; NA: 36%) and multi-vitamin supplements (A: 40%; NA: 29%) were the most often used vitamins. The main reason for DS intake was for health improvement (A: 77%; NA: 71%). The main information source was cited as their parents (A: 66%, NA: 71%).Discussion: Young German athletes beginning their sporting career show similar supplementation habits astheir non-athletic counterparts. Compared to the literature, prevalence of DS use amongst the observed athletes is low. This is likely to increase with age and growing performance level. Keeping that and possible doping infractions or overdoses in mind, nutritional education should start early in ones sporting career and should include the parents.KEY WORDS: Dietary Supplement, Nutritional Supplement, Elite Athlete, Adolescent, Sports Nutrition, Non-Athlete